To Imitate the Trinity in Augustine’s Theology - Lee, Sang Hoon ca. 21. Jh. (Heythrop journal, 2025)
During the heyday of social trinitarian theologies, numerous proposals were offered, envisioning the eternal communion of the Trinity as a paradigm for human communities. However, with the ebbing influence of social trinitarianism, the doctrine of the Trinity is now rarely invoked as the foundation of social visions. Aware that both in the past and today, Western trinitarian theology—such as Augustine’s—does not lend itself to social visioning, this article seeks to show that Augustine himself urged his readers to imitate the Trinity and thus offers a theological foundation for a social vision. Following an exploration of Augustine’s theological exhortation, the article will also examine its modern applications in the works of John Milbank and Sarah Coakley.